The Effect of Canva Application on Students’ Motivation and Engagement in Writing Among Senior High School - Tri Rahayu; Hastini Hastini (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
The aim of this research is to find out the effect of using Canva application on students’ writing motivation and engagement of the eleventh-grade students at SMA Labschool Untad Palu with a sample of 42 students from two classes: XI MIA 2 and XI IIS. This research used a quantitative method with an ex post facto design. Data were collected using a questionnaire and analyzed through descriptive statistics and simple linear regression using SPSS 26. The findings showed that the use of Canva had a significant and positive effect on students' writing motivation and engagement. The regression results revealed that Canva influenced intrinsic motivation (Sig. = 0.004; R² = 19.1%), extrinsic motivation (Sig. = 0.001; R² = 23.4%), and engagement (Sig. = 0.040; R² = 10.1%). Most students also showed a preference for creating Procedure Texts with Canva. In conclusion, Canva is effective digital tool on students' motivation and engagement in writing. Therefore, it is recommended for use in English learning to make writing activities more interesting and interactive.